2023
DOI: 10.1002/nano.202300116
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon microneedle patches for delivery of polymyxin‐based antimicrobials

Nazia Tabassum,
David Rudd,
Li Yan
et al.

Abstract: There is a global trend of increasing antibiotic resistance to Gram‐negative bacteria and the medical research community is looking for alternative antibiotics. Antibiotics such as polymyxin B (PMB) show excellent efficacy and low resistance rates against Gram‐negative bacteria. The topical administration of PMB, however, has clinical limitations such as minimal residence time, making it difficult for its use to treat skin infections. Here, we present porous silicon microneedle (pSi MN) patches to deliver PMB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Voelcker, Alba and colleagues, developed porous silicon microneedle patches to deliver polymycin B to the skin to treat bacterial infections [28]. After loading the drug into the porous layer, the authors demonstrated the antibacterial activity of the porous silicon microneedles against Gram-negative Escherichia coli and their potential for antimicrobial applications using the transdermal drug delivery approach.…”
Section: Areas Covered In the Special Topicmentioning
confidence: 99%
“…Voelcker, Alba and colleagues, developed porous silicon microneedle patches to deliver polymycin B to the skin to treat bacterial infections [28]. After loading the drug into the porous layer, the authors demonstrated the antibacterial activity of the porous silicon microneedles against Gram-negative Escherichia coli and their potential for antimicrobial applications using the transdermal drug delivery approach.…”
Section: Areas Covered In the Special Topicmentioning
confidence: 99%